Atribuição de causalidade ao nível de competência em jogadores de futebol - Sá, Lucas Guimarães Cardoso de (2009)
The motivational model of causal attribution predict that emotions and expectations, generated by the type of cause utilized by a person to explain what happens to himself, can influence his motivation. All causes could be classified according to three dimensions: locus of causality, stability and controllability. Studies have showed that in sports situations there is a tendency to attribute positive or successful results to internal, stable and controllable causes and negative or failed results to external, unstable and uncontrollable causes. Thus, this study was developed with the aim to investigate the causes attributed by juniors and amateur adults football players to their competence level and to verify the influence generated on their emotions, expectations and dispositions to action. The study was composed by 189 football players, being 111 juniors and 78 amateur adults. A structured interview with 47 questions about causal antecedents, causal ascriptions, causal dimensions, emotions, expectations and dispositions to action was used. The results showed that as adults as juniors with high competence level made more internal, more stable and equally personal controllable attributions, when comparing to those with low competence level, that used more external, unstable and also personal controllable causes. The different kinds of attribution, otherwise, generated similar consequences, since the means of positive emotions, expectations and dispositions to action kept equally high. This may be a clue that athletes use the attribution process as a way to defend themselves from unpleasant emotions and expectations, which could take them to undermine their motivation. Thus, the conclusion is that football players of this sample used what others studies named optimistic attributions, those in which what is perceived as good is explained in a way that keep being like this and what is perceived as bad can be better in the future.